A novel RING finger gene, SbRFP1, increases resistance to cold‐induced sweetening of potato tubers. Issue 6 (8th February 2013) - Zhang, Huiling; Liu, Xun; Liu, Jun; Ou, Yongbin; Lin, Yuan; Li, Meng; Song, Botao; Xie, Conghua
Abstract : The modulation of the activity of enzymes associated with carbohydrate metabolism is important for potato cold‐induced sweetening (CIS). A novel RING finger gene SbRFP1 was cloned and its expression was found to be cold‐inducible in potato tubers of the CIS‐resistant genotypes. Transformation of SbRFP1 in potatoes confirmed its role in inhibiting β‐amylase and invertase activity, which consequently slowed down starch and sucrose degradation and the accumulation of reducing sugars in cold stored tubers. These findings strongly suggest that SbRFP1 may function as a negative regulator of BAM1 and StvacINV1 to decelerate the accumulation of reducing sugars in the process of potato CIS. Abstract : ► A novel C3 HC4 ‐type RING finger gene, SbRFP1, was cloned from potato. ► SbRFP1 plays crucial roles in potato cold‐induced sweetening. ► SbRFP1 functions as a negative regulator of BAM1 and StvacINV1 . ► It is the first report that RING finger protein contributes to potato CIS.